Men's Intimate Partner Violence against Sami Women: A Swedish Blind Spot - Burman, Monica (Umeå University Library, 2017)
The aim of this article is to map the Swedish context regarding men’s intimate partner violence against Sami women and (1) discuss what knowledge and perspectives that dominates that context, and (2) reflect upon possible starting points for meeting the need for knowledge. The outline shows that men’s intimate partner violence against Sami women is a blind spot in Sweden. Important aspects, such as human rights and colonialism, are neglected in the policy discourse. At the most, the policy discourse includes abused Sami women in the problematic category “particular vulnerable groups”. The author argues for a need to problematize if and how responsibility is taken for addressing and responding to the violence and suggests a postcolonial and intersectional approach that centers around how the imbalance of power and control runs through abused women’s experiences. Finally, the author highlights how such an approach also is a matter of indigenous research ethics.